Principals’ Competence in Performance Management of Private Secondary School Teachers in the Division of Nueva Ecija - Galang, Julieta P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Teacher quality is the most important factor influencing student achievement, highlighting the key role of teachers in improving learner outcomes. Managing teacher performance is essential to enhancing teaching quality. Therefore, principals must continually develop their skills in planning, monitoring, and reviewing to effectively manage teacher performance. This study determined and described the principals’ competence in performance management of teachers in the private secondary schools in the Division of Nueva Ecija. The descriptive method of research was employed in the study. Survey instruments in the form of questionnaires were distributed to thirty-six (36) principal- respondents, thirty-three (33) department heads and two hundred one (201) teachers. The findings clearly indicate that all the respondents displayed common perceptions on the principals’ competence in managing the performance of teachers, and considered performance management as a means for quality improvement in educational practice to ensure better teaching and learning has taken place in the classroom. The findings, however, showed that there was a significant difference between and among the perceptions of the respondent- principals, department heads and teachers on the level of principals’ competence in teacher performance management only in the area of monitoring. The overall findings of the study reflected that the principals were highly competent in the three areas of performance management: planning, monitoring and reviewing performance of teachers. Hence, there is only a need to sustain principals’ competence in teacher performance management.